SPECIFIC FEATURES OF BLOOD SUPPLY AND INTRAORGANIC MICROCIRCULATORY STREAM OF HUMAN SUBMANDIBULAR VEGETATIVE GLAND - Polovyk О.Yu. (World of Medicine and Biology, 2015)
Older people are often found trigeminal nerve and nodes disease’s, accompanied by versatile symptoms manifested vegetative-vascular, trophic disorders and paine, complicating diagnosis and rational choice of treatment. In semysin serial sections during mandibular vegetative node detected arterial microvessels, which in connective membranes departing from the capsule penetrate deep into the hub of the hub. Investigation of the topography confirm that a closed annular principle of organization intraorganic a blood microcirculation and significant for contact between capillaries, postcapillary venules and neurocyts ensure the continuing operation of the site as a body and is essential for providing transport facilities for age restructuring of this node.